PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, ETOS KERJA DAN KOMPETENSI TERHADAP KINERJA GURU (STUDI PADA YAYASAN TARBIYATUL ISLAM NW WANASABA LOMBOK TIMUR) - Lalu Abdul Hafidz; Agusdin Agusdin; Hermanto Hermanto (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2020)
As the power of educating, teaching, guiding, directing, training, evaluating, and evaluating student teacher performance will be very supportive. One way to improve teacher performance is to pay attention to factors that can improve teacher performance. Paying attention to the factors that affect the teacher's performance delivered by Gibson, its relation to teacher performance at the Tarbiyatul Islam Foundation Nahdlatul Wathan Wanasaba as an object of research will be seen from three variables; (1) organizational variables related to leadership; (2) psychological variables include personality in the form of work ethic and (3) individual variables include the ability or competence of teachers.Based on the above circumstances, the purpose of this study is to analyze and determine the effect of transformational leadership, work ethics and competency in a pasial (separate) and simultaneously (together) manner on teacher performance at the Tarbiyatul Islam NW Wanasaba East Lombok Foundation. To meet these objectives, multiple linear regression analysis is carried out, namely t test and F test. Before conducting multiple linear regression analysis, first classical assumptions are tested of all variables that are valid and reliability. Finally, interpret the results and conclusions.After multiple linear regression analysis is done, the result that is spatially and simultaneous transformational leadership, work ethic and competence significantly affect the performance of teachers at the Islamic Foundation NW Wanasaba Tarbiyatul East Lombok.Keywords :independent variable, dependent variable, Partial, simultaneous